Caesarean section: its rates and indications at a tertiary referral center in Eastern Nepal - Chhetri, S; Singh, U (Health Renaissance, 2011)
Background: There has been a sustained increase in the rate of caesarean section in the last few years around the world. Data regarding the current caesarean rate and the trends of its indications in eastern Nepal have not been estimated earlier. Aim: To assess the rate of caesarean sections and the varying indications for caesarean section in a tertiary referral center in eastern Nepal. Methods: All hospital deliveries that took place in BPKIHS between January 2006 and December 2007 were recorded to assess the caesarean section rate and its indications. Results: A total of 5330 deliveries were conducted in 2006. Likewise the total number of deliveries conducted in 2007 was 6634. In 2006 caesarean sections were performed in 28.6% (1524) of all patients. The rate of caesarean sections in 2007 increased and was 33.7% (2239). The most common indication for caesarean section was meconiumstained liquor, which constituted 23.4% (883). The next frequent indication was previous caesarean section, which accounted for 17.2% (650), followed by breech presentation in 11.1% (417), fetal distress in 9.6% (364), non-progress of labor in 7.2% (270), cephalopelvic disproportion in 6.2% (234, and placenta previa in 4.4% (165). Conclusions: There is a increasing trend of performing cesarean section in the tertiary referral center in east era Nepal. The most common indication for cesarean section is meconium-stained liquor. Keywords: Caesarean section; caesarean delivery rates; Nepal DOI: http://dx.doi.org/10.3126/hren.v9i3.5587 HR 2011; 9(3): 179-183